Bridging the digital divide: Measuring digital literacy - Krish Chetty; Liu Qigui; Nozibele Gcora; Jaya Josie; Li Wenwei; Chen Fang (Kiel Institute for the World Economy (IfW), 2017)
To promote digital transformation, equal emphasis needs to be placed on digital skills development as to infrastructure development. Integral to investment in digital skills development is the subsequent management and evaluation of digital training programmes. This paper assesses mechanisms to ensure digital training programmes are adequately managed using a standardized data collection framework to measure an internationally accepted digital literacy index. Such an index must be defined by an agile definition of digital literacy responsive to the fluid nature of the digital economy. The paper also explores the extent to which a G20 advisory body may inform a nationally representative data collection strategy within the context of a data collection process that is cognizant of the evolving demands of businesses and users alike.
Keywords: C83; J20; J22; J23; J24; F63; F66; F68; I24; I25; O15; O19; 330; Digital literacy; digital skills; digital divide; digitalization; information literacy; computer literacy; media literacy; communication literacy; technology literacy; agile policy making; representative sampling